31 Learning from hospice experiences of withdrawing continuous artificial nutrition and hydration in patients with prolonged disorders of consciousness. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Lewis, Heledd; Carr, Madeleine; Seaman, Siwan
Abstract : Background: Following The Supreme Court judgement it is no longer mandatory to involve the court to make best interest decisions to withdraw clinically assisted nutrition and hydration (CANH) in patients with prolonged disorders of consciousness (PDOC). We anticipate a higher number of patients being admitted to the hospice setting for end of life care for this indication. Method: Reviewed case notes of patients, with a diagnosis of PDOC, admitted to our hospice for discontinuation of CANH and analysed the content of interviews with multi-disciplinary health care professionals who had been involved in managing and caring for these patients. Results: Two patients with PDOC were admitted to the hospice over a 12 month period for withdrawal of CANH. A 28-year-old man who had been in a vegetative state for 15 months secondary to a cerebral abscess and a 73-year-old woman who had been in a vegetative state for 6 years following a hypoxic brain injury. They both died at the hospice 9 days after discontinuing CANH. Key themes identified were educational needs of hospice staff especially an understanding of how reflex reactions may be misunderstood as purposeful actions in PDOC, the value of providing an opportunity for staff to debrief following episodes of care and the importance of the hospice team being involved in the development of a detailed end of life plan prior to hospice admission. Conclusion: There are numerous medical, ethical and legal challenges encountered in making the decision to withdraw CANH and then in providing end of life care for these patients. Learning from our work may help other professionals caring for similar patients as we predict an increase in referrals to hospices to be involved in managing the care of similar patients.